Macroeconomic consequences of international labour migration: Simulation experience from an econometric disequilibrium model - Werner Smolny (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
Recent experience on increasing labour supply Coming from outside the FRG enhances interest in the economic effect of these supply shocks. This paper analyses the consequences of guest workers Immigration in the sixties and seventies using a macroeconometric disequilibium model. Within the rationing context the derivation of nonlinear multipliers is facilitated, which depend on the shares of demand and supply constrained regimes prevailing in the economy. The immediate impact stems from prevention of wage and price inflatioa by increasing labour supply. Effects on Investment, the adjustment of the capital - labour ratio, and productivity have also to be discussed. In this context a shadow price of the labour supply constraint is derived. The model is estimated for the FRG and some simulations are performed. First, a restrictive immigration policy is modeled concerning guest workers coming from non EC - countries in the late sixties, i.e. a prosperous period, and these results are compared with simulations of a reduction of labour supply in the less prosperous period of the eighties.
Keywords: 330